2015
DOI: 10.1117/12.2078638
|View full text |Cite
|
Sign up to set email alerts
|

Gold sputtered Blu-Ray disks as novel and cost effective sensors for surface enhanced Raman spectroscopy

Abstract: Surface Enhanced Raman spectroscopy (SERS) offers sensitive and non-invasive detection of a variety of compounds as well as unparalleled information for establishing the molecular identity of both inorganic and organic compounds, not only in biological fluids but in all other aqueous and non-aqueous media. The localized hotspots produced through SERS at the solution/nanostructure interface of clustered gold or silver nano-particles enables detection levels of parts per trillion. Recent developments in advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nieuwoudt gratings of a BD to create inexpensive substrates for surfaceenhanced Raman spectroscopy. 25 Smith et al has "repurposed" Blu-ray movie discs as quasi-random nanoimprinting templates for photon "management" in the patterned metal electrodes for solar cells. 26 Recently, Maquieira and co-workers have demonstrated their enzyme inhibition microassays on BDs for drug discovery based on a physical immobilization (passive adsorption) approach.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nieuwoudt gratings of a BD to create inexpensive substrates for surfaceenhanced Raman spectroscopy. 25 Smith et al has "repurposed" Blu-ray movie discs as quasi-random nanoimprinting templates for photon "management" in the patterned metal electrodes for solar cells. 26 Recently, Maquieira and co-workers have demonstrated their enzyme inhibition microassays on BDs for drug discovery based on a physical immobilization (passive adsorption) approach.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, only limited studies have been reported in exploring BDs for materials and analytical chemistry applications. Nieuwoudt et al sputtered gold films on the nanostructured gratings of a BD to create inexpensive substrates for surface-enhanced Raman spectroscopy . Smith et al has “repurposed” Blu-ray movie discs as quasi-random nanoimprinting templates for photon “management” in the patterned metal electrodes for solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…Arnadis-Chover et al has modified a Blu-ray drive by incorporating an external amplification/detection board for reading disc-based high-density DNA hybridization arrays and competitive immunoassays for microcystins . Nieuwoudt et al sputtered gold films on the nanostructured gratings of a BD to create inexpensive substrates for surface-enhanced Raman spectroscopy . Donolato et al converted a Blu-ray optical pick-up unit into an optomagnetic reading device to monitor the Brownian relaxation dynamics of modified magnetic nanoparticles in microfluidic devices for the quantitation of E. coli DNA .…”
mentioning
confidence: 99%